HORIZONTAL CONFLICT DYNAMICS AND ITS RESOLUTION: HORIZONTAL CONFLICT STUDY IN KALIREJO VILLAGE, KULON PROGO REGENCY - An'Amta, dimas Asto Aji (Universitas Lambung Mangkurat, 2023)
The precious metal in the form of gold in Kalirejo Village has brought disaster. As there is a horizontal conflict, namely conflict among citizens. The purpose of this paper is to look at the dynamics of horizontal conflict and its resolution in Kalirejo Village using Moore's triangle of statistics approach. This research uses a qualitative method, namely analytical descriptive with a collective case study strategy to look at the conflicts that occurred in the period from 2009 to 2014. The result is that the dynamics of conflict over natural resources at the horizontal level cannot be avoided. Whereas the conflict resolution offered does not get satisfaction from one party who is harmed both in a transparent, procedural, and psychological way that has been done on this conflict phenomenon